Hubungan Tingkat Pengetahuan Dan Sikap Dengan Perilaku Vulva Hygiene Pada Remaja Putri Saat Menstruasi Di Kelas X Di SMA Perguruan Rakyat 2 Jakarta Timur Tahun 2023 - Amelia Rospika Jatimineng; Yani Handayani; Nurul Ainul Shifa (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
The menstrual period is the initial door for young women to know about reproductive organs. One that steals attention is related to maintaining the outer feminine area known as vulva hygiene. The purpose of this study is to determine the relationship between knowledge and attitudes towards vulva hygiene behavior in adolescent girls in class X with the population is 90 people. This type of research is a correlation descriptive quantitative research. With the type design is a cross sectional. Bivariat analyze that using spearman – rank, with the result therea are correlation between knowladge level and attitude is ( p – value – 0,000) and nothing corellation beetween attitude with behaviour is ( p – value = 0, 114 ) . the cunclution is : there are correlation between knowladge level and attitude and nothing correlation between attitude with bevaviour vulva hygiene in adolescent girl durig menstruation in class X